Sztuka w przestrzeni społecznej – wymiar artystyczny i edukacyjny - Rzymełka-Frąckiewicz, Agata; Wilk, Teresa (Chowanna, 2020)
The present text is an attempt to draw social attention to the place and role of art in the social/public space, and thus the artistic and social impact of art arranged in this space. Art, apart from its artistic and aesthetic value, has a social-educational and utilitarian value. Presenting works of art in public space can not only revise the way of thinking about art / perception of art, but also develop the need to implement its potential in everyday life. The artistic and social dimension of art is a peculiar configuration of good, truth and beauty – values so socially desirable.